Managing Capital Flows in Asia: An Overview of Key Issues - James Villafuerte; Josef T. Yap (Asian Development Bank (ADB), 2015)
Global capital flows into emerging markets, including those in Asia, continue to be volatile. These capital flows generate both benefits and costs. The latter are associated with episodes of currency and banking crises like the 1997 Asian financial crisis and the 2008 global financial and economic crisis. Policy responses can be implemented to minimize the costs. At the same time, policy responses should vary depending on whether "pull" factors or "push" factors dominate the capital flows. Data show that the main impact of capital flows on economies of East Asia is reflected in real effective exchange rates, equity prices, and accumulation of foreign exchange reserves. If "pull" factors are dominant, policy makers should allow real exchange rates to appreciate in the long-term. Three broad categories of macroeconomic measures are available to countries facing surges of capital inflows, if they are not willing to allow the nominal exchange rate to appreciate: (i) sterilized intervention, (ii) greater exchange rate flexibility, and (iii) fiscal tightening (preferably through expenditure cuts). However, all of them have major drawbacks. Instead, capital controls or, more generally, macroprudential policy can be considered. Other policy recommendations include measures to encourage foreign direct investment, as this type of capital flow is more stable and beneficial; exchange rate coordination to reduce the adverse impacts of currency appreciation on the global competitiveness of domestic firms; and regional financial cooperation, particularly in the development of local bond markets. Recent data show the adverse impact of Quantitative Easing tapering on Asian economies. This is verified by econometric results showing the strong linkages between the United States bond markets and those in Asia. These findings enhance the role of macroprudential policy, which can be implemented in the context of regional cooperation in order to reduce negative spillovers across economies in Asia.
hdl:11540/5271
Keywords: F31; F32; F36; 330; capital flows; exchange rates; regional cooperation; volatility